A DESCRIPTIVE STUDY ON STUDENTS’ SPEAKING ABILITY IN “DAILY CONVERSATION” CONTEXT AT HIGHER EDUCATION - Nurlaela Nurlaela; Yuliana Mangendre (JURNAL PENDIDIKAN GLASSER, 2023)
Speaking is one of English skill that has been learnt from junior high school until higher education. It means that students in higher education should have good capability in doing speaking in all contexts, include in daily conversation context. For this reason, this study was designed to determine the extent to which students' ability in speaking especially in daily conversation context. This study took 22 students in Educational Faculty of Tompotika Luwuk University as the participants. Descriptive qualitative is a method that chosen in this study. The data have been collected from observation and documentation. Observation and documentation collected when the students doing conversation. The result of this study shows that the students’ speaking ability in daily conversation context can be categorized into “poor”. It was proven by the students who got only 18,18% in good category, 22,72% in average category, 40,92% in poor category, and 18,2% in very poor category. Finally, it can be conclude that the students’ speaking ability in daily conversation context at higher education of Educational Faculty of Tompotika Luwuk University categorized into poor.